Schultz index of zigzag polyhex nanotubes - Eliasi, Mehdi,; Taeri, Bijan, (Utilitas Mathematica, 2007)
Schultz index of a molecular graph G is defined as 1/2 ∑ {u,v}⊂V(G)(deg (u) + deg (v))d(u,v), where d(u,v) is the distances between u and v in the graph G and deg (u) is the degree of the vertex u. In this paper we find an exact expression for Schultz index of TUHC6[2p,q], the zigzag polyhex nanotubes.